2015
DOI: 10.13188/2377-987x.1000008
|View full text |Cite
|
Sign up to set email alerts
|

Serpine1 Mediates Porphyromonas gingivalis Induced Insulin Secretion in the Pancreatic Beta Cell Line MIN6

Abstract: Periodontitis is an inflammatory disease resulting in destruction of gingiva and alveolar bone caused by an exuberant host immunological response to periodontal pathogens. Results from a number of epidemiological studies indicate a close association between diabetes and periodontitis. Results from cross-sectional studies indicate that subjects with periodontitis have a higher odds ratio of developing insulin resistance (IR). However, the mechanisms by which periodontitis influences the development of diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Type 2 diabetes is a metabolic disease that is a major public health problem worldwide. The bidirectional association between periodontitis and diabetes has been widely accepted ( Lalla and Papapanou, 2011 ).Results of cross-sectional studies have shown that patients with periodontitis have a higher incidence of insulin resistance (IR) ( Bhat and Watanabe, 2015 ). Insulin resistance is an important cause of type 2 diabetes mellitus (T2DM) ( Tian et al., 2020 ).…”
Section: Association Of P Gingivalis With Systemic...mentioning
confidence: 99%
“…Type 2 diabetes is a metabolic disease that is a major public health problem worldwide. The bidirectional association between periodontitis and diabetes has been widely accepted ( Lalla and Papapanou, 2011 ).Results of cross-sectional studies have shown that patients with periodontitis have a higher incidence of insulin resistance (IR) ( Bhat and Watanabe, 2015 ). Insulin resistance is an important cause of type 2 diabetes mellitus (T2DM) ( Tian et al., 2020 ).…”
Section: Association Of P Gingivalis With Systemic...mentioning
confidence: 99%
“…In animal models, periodontitis induction is associated with hyperinsulinemia [90], suggesting a direct impact of periodontal bacteria on the function of pancreatic β-cells, the only known source of circulating insulin. In the murine pancreatic β-cell line MIN6, P. gingivalis and its LPS induce an increase in insulin secretion [108] associated with the elevation of SerpinE1 gene expression [109]. The serpinE1 gene encodes the plasminogen activator inhibitor-1 (PAI-1), which is known to increase during obesity, insulin resistance and diabetes [110].…”
Section: Pancreatic β-Cellsmentioning
confidence: 99%